2020
DOI: 10.1186/s40842-020-00113-4
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly and thyroid cancer: analysis of evolution in a series of patients

Abstract: Background Acromegaly is associated with higher morbidity and mortality mainly due to cardiovascular disease. Data on the incidence and evolution of thyroid cancer in acromegaly are controversial. Our objective was to describe the characteristics of a group of acromegalic patients with differentiated thyroid carcinoma (DTC) and analyze their evolution. Methods This is a retrospective multicenter study of 24 acromegalic patients with DTC. The AJCC S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(41 reference statements)
0
4
0
1
Order By: Relevance
“…La acromegalia es una patología crónica de naturaleza progresiva lenta, como consecuencia de los síntomas no específicos [3], tardando varios años en ser diagnosticada, algunos autores refieren como promedio 10 años [4,5], reflejo de esta demora resulta que hasta el 80% son macroadenomas al diagnóstico [6], y la sintomatología con la que debutan puede estar Figura 2 RMN S/C de hipófisis: posquirúrgico. ocasionada por la naturaleza expansiva del tumor [5], motivando la realización de estudios complementarios en los que se filie la masa pituitaria, además de la evaluación bioquímica con el perfil hormonal siguiendo el algoritmo diagnostico con IGF-1 superior a 2.5 DE y falta de supresión de la GH a la hiperglucemia [7].…”
Section: Discussionunclassified
“…La acromegalia es una patología crónica de naturaleza progresiva lenta, como consecuencia de los síntomas no específicos [3], tardando varios años en ser diagnosticada, algunos autores refieren como promedio 10 años [4,5], reflejo de esta demora resulta que hasta el 80% son macroadenomas al diagnóstico [6], y la sintomatología con la que debutan puede estar Figura 2 RMN S/C de hipófisis: posquirúrgico. ocasionada por la naturaleza expansiva del tumor [5], motivando la realización de estudios complementarios en los que se filie la masa pituitaria, además de la evaluación bioquímica con el perfil hormonal siguiendo el algoritmo diagnostico con IGF-1 superior a 2.5 DE y falta de supresión de la GH a la hiperglucemia [7].…”
Section: Discussionunclassified
“…What is noteworthy, the prevalence of thyroid neoplasms among patients with acromegaly is comparable in males and females. [61] and the data show that there is no difference in the aggressiveness of thyroid carcinoma between patients with acromegaly and the control group [62]. Studies showed that 25% to 90 % of acromegalic patients manifested goitre and 65 % had multinodular goitre, which shows the positive correlation between the GH and IGF-1 levels and thyroid volume [62].…”
Section: Thyroid Carcinomamentioning
confidence: 95%
“…[61] and the data show that there is no difference in the aggressiveness of thyroid carcinoma between patients with acromegaly and the control group [62]. Studies showed that 25% to 90 % of acromegalic patients manifested goitre and 65 % had multinodular goitre, which shows the positive correlation between the GH and IGF-1 levels and thyroid volume [62]. To understand the linkage between the thyroid benign and malignant nodules emergence in the course of acromegaly, the molecular aspects need to be highlighted.…”
Section: Thyroid Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Biological evidence of close relationships between the two axes are mainly based on clinical observations in GH-deficient patients treated with rhGH at physiological doses and also in opposite circumstances-in acromegalic patients with pathological GH excess, in whom the thyroid gland is often affected. In patients with supraphysiological level of GH, goiter is reported in 55-87% [39,40] and thyroid cancer in 8.7-10.6% [41][42][43].…”
Section: Mechanisms Explaining the Gh/igf-1 Effect On The Hpt Axismentioning
confidence: 99%